Do Self-Efficacy, Financial Literacy, and Digital Literacy among Students Contribute to Entrepreneurial Behavior through Entrepreneurship Education? - Andi Syahriana Asdar; Sitti Hasbiah; Mulyadi AR (Pinisi Journal of Entrepreneurship Review, 2024)
This research aims to determine the direct and indirect influence of self-efficacy, financial literacy, and digital literacy on entrepreneurial behavior through entrepreneurship education among entrepreneurship study program active students from the 2019 to 2023 class of Makassar State University. The research method used in this research is quantitative. The population in this study was all students at Makassar State University for the 2023/2024 academic year with a total sample of 104 students. Based on the results of the research that has been carried out, this research can be a source of information or reference for teaching staff or lecturers so that they can direct and guide students regarding developing someone's behavior towards entrepreneurial desires. Students are expected to be able to further deepen their entrepreneurial education related to business management so that it is not focused on only on the scientific theory produced, but also able to carry out business ventures and develop them. For further research, efforts will be made to deepen and expand this research both in terms of variables and development of research methods.